Publication ethics statement for the year 2025 (Vojnotehnički glasnik / Military Technical Courier, 2025)
The publication of an article in this peer reviewed journal is an essential model for the scientific journal Military Technical Courier. It is necessary to agree upon standards of expected ethical behavior for all parties involved in the act of publishing: the author, the journal editor, the peer reviewer and the publisher. The editorial policy of the Military Technical Courier is based on the COPE Core Practices, common COPE, DOAJ, OASPA and WAME Principles of Transparency and Best Practice in Scholarly Publishing as well as on the best accepted practices in scientific publishing. The Military Technical Courier has been a COPE (Committee on Publication Ethics) member since 2nd May 2018 and a member of OASPA (Open Access Scholarly Publishers Association) since 27th November 2015. The editorial office applies Checklist for open access publishers on implementing the UNESCO Recommendation on Open Science. This document is part of the UNESCO Open Science Toolkit, designed to support implementation of the UNESCO Recommendation on Open Science. It has been produced in partnership with OASPA.